In Thyroidectomized Thyroid Cancer Patients, False-Positive I-131 Whole Body Scans Are Often Caused by Inflammation Rather Than Thyroid Cancer. (25th February 2016) - Garger, Yana Basis; Winfeld, Mathew; Friedman, Kent; Blum, Manfred
Objective. To show that I-131 false-positive results on whole-body scans (WBSs) after thyroidectomy for thyroid cancer may be a result of inflammation unassociated with the cancer. Methods. We performed a retrospective image analysis of our database of thyroid cancer patients who underwent WBS from January 2008 to January 2012 to identify and stratify false positives. Results. A total of 564 patients underwent WBS during the study period; 96 patients were referred for 99 I-131 single-photon emission computed tomography (SPECT/CT) scans to better interpret cryptic findings. Among them, 73 scans were shown to be falsely positive; 40/73 or 54.7% of false-positive findings were a result of inflammation. Of the findings, 17 were in the head, 1 in the neck, 4 in the chest, 3 in the abdomen, and 14 in the pelvis; 1 had a knee abscess. Conclusions. In our series, inflammation caused the majority of false-positive WBSs. I-131 SPECT/CT is powerful in the differentiation of inflammation from thyroid cancer. By excluding metastatic disease, one can properly prognosticate outcome and avoid unnecessary, potentially harmful treatment of patients with thyroid cancer.